Peran Sosiologi Pendidikan dalam Mewujudkan Keadilan Sosial pada Lembaga Pendidikan yang Inklusif di Era Digital - Maulidina Akmal; Rosalina Rosalina; Nur Khasanah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Education, as a social institution, plays a strategic role in creating social justice, particularly through the implementation of inclusivity principles. In the digital era, challenges and opportunities for educational institutions have become increasingly complex, as technological advancement influences access, methods, and learning interactions. This study aims to analyze the role of the sociology of education in realizing social justice within inclusive educational institutions in the digital age. The research employs a library research method by reviewing various academic sources, including textbooks, accredited national journals, and recent scientific articles relevant to the topic. The results indicate that the sociology of education plays a crucial role in understanding social relations within educational institutions and in constructing an equitable and fair learning system. Inclusive education serves as a concrete manifestation of social justice values by accommodating the needs of all learners without discrimination (Setiawan & Cipta Apsari, 2023). Furthermore, digital technology contributes to inclusivity through assistive technologies, adaptive online learning, and the development of digital literacy among teachers and students (Tanjung et al., 2022). Therefore, the sociology of education provides a critical perspective for realizing an educational system that is fair, humanistic, and adaptive to social changes in the digital era.